AN INVESTIGATION OF TRANSLANGUAGING PRACTICES IN EFL CLASSROOM: A MULTIPLE CASE STUDY OF JUNIOR HIGH SCHOOLS IN KOTAMOBAGU - Sukirman, Firjinia Putri Utami; Maru, Mister Gidion; Liando, Nihta V. F. (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
The present study aims at investigating the implementation of translanguanging as a pedagogical approach in EFL classroom from perception and experiences of the teachers and students in Junior High School in Kotamobagu This study employs a qualitative approach specifically a case study The data sources consisted of 2 English teacher and 40 students from two classes 20 students per class selected through purposive sampling technique For this case there are three data collection methods which are: Classroom observation Semi structured interview and Documentation The data analysis was guided by thematic analysis consists of: transcribing reading and tagging open coding thematic identification and thematic reviewing deepening and interpretation The results have shown the implementation of pedagogical translanguaging contributes significantly because it helps students build an inclusive classroom environment through the use of classroom linguistic resources In addition educators and students have equal perspective on the translanguaging approach compared to the monolingual method to reduce affective barriers in the context of proficiency and preparation for global communication The study indicates that transcoding practices affect English language learning especially in areas of inclusive practice vocabulary etc Integrated practices promote inclusive growth while the monolingual approach encourages setbacks in fluency listening and overall communicative competence This why study assumes that teacher who use translanguaging in pedagogy can understand that students anxiety in English as a Foreign Language EFL lessons decreases thereby encouraging student participation in learning < p>